A Study of Single Stone Column Bearing Capacity from a Full-Scale Plate Load Test in Long Son Project - Dang, Hong Lam (Engineering, Technology & Applied Science Research, 2024)
The ultimate bearing capacity of stone columns is very important in the design of soil improvement. The bulging failure mechanism is the most common failure mechanism reported. However, it depends on the surrounding soil at the site, necessitating a site-specific study of single-stone column bearing capacity. The current paper presents the full-scale plate load test of the single stone column in the Long Son Petrochemical Project, Vietnam in order to verify the bearing capacity of single stone column. A single stone column of 800 mm diameter was installed at the site by vibroflot. An 800 m circle full-scale plate test was carried out on site. The stone properties followed the Vietnamese standard TCVN 7572. The settlement result of the plate load test verifies the single stone column bearing capacity of 882.5 kPa.